External Factors That Affect Operational Performance: A Conceptual Model Development for Pharmaceutical Drug Wholesalers Companies in Bali, Indonesia - Komang Agus Satria Pramudana; Ni Nyoman Kerti Yasa; Ni Wayan Ekawati; Putu Yudi Setiawan (International Journal of Social Science and Business, 2023)
Pharmaceutical distributor companies or also known as PBF (Pharmaceutical Drug Wholesalers) play an important role in the distribution of pharmaceutical products in Indonesia. Without the role of PBF, the drug will not reach the patients from the manufacturer. The PBF appointed by the manufacturer to distribute the product, has operational performance targets that must be achieved. However, like other businesses, PBF operational performance is also affected by external factor, such as the Covid-19 pandemic.  The purpose of this study was to analyze the impact of external factors, those are: Covid-19 pandemic, government regulations and the intensity of competition on the operational performance of PBF in Bali. This study uses the literature review method. Data analysis in the literature review involves compiling and presenting findings from various data sources that have been collected. The result of this research is a conceptual model that synergizes sales strategy and operational control as mediating and moderating variables to minimize the negative impact of external factors on operational performance. This research is expected to contribute to the field of strategic management, particularly related to the supply chain of pharmaceutical products.